2017
DOI: 10.1007/s13744-017-0498-y
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Aedes sp. Linnaeus (Diptera: Culicidae) and Associated Entomofauna in Bromeliads from a Forest Patch within a densely Urbanized Area

Abstract: Little is known about the relationship between the presence of Aedes, abiotic factors and the entomofauna existing in phytotelmatas. The aim of this study was to identify biotic and abiotic factors associated with the presence of Aedes in bromeliads sites located in a forest fragment in Rio de Janeiro, Brazil. In the study area, eight bromeliads from the Aechmea genus were chosen and kept in landscape form. Physical and chemical variables were measured. Collected aquatic insects were identified according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…albopictus was statistically positively influenced by temperature. This result corroborates the studies by Calado and Navarro-Silva 42 and Docile et al 43 , who found this species to be more frequent in breeding sites with high temperatures. However, the other vector species were not statistically significantly influenced by the climatic variables tested.…”
Section: Discussionsupporting
confidence: 93%
“…albopictus was statistically positively influenced by temperature. This result corroborates the studies by Calado and Navarro-Silva 42 and Docile et al 43 , who found this species to be more frequent in breeding sites with high temperatures. However, the other vector species were not statistically significantly influenced by the climatic variables tested.…”
Section: Discussionsupporting
confidence: 93%
“…albopictus was associated with temperature. Docile et al (2017) observed that this species had a strong association with the temperature and pH when collected in bromeliads. Medeiros-Sousa et al (2013) stated that some species of mosquitoes collected in areas of city parks show predatory behavior, as is the case of Toxorhynchites, which play the role of immature controllers in their breeding sites.…”
Section: Discussionmentioning
confidence: 91%
“…These findings reveal an ecological phenomenon structuring the population distribution, with competition possibly playing a role in the observed patterns, which structured the observed combination of species. Docile et al [ 40 ] reported that immatures collected from bromeliads presented a structured distribution of specimens, not following a random pattern.…”
Section: Discussionmentioning
confidence: 99%